2008
DOI: 10.1016/j.visres.2008.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Radial frequency adaptation suggests polar-based coding of local shape cues

Abstract: The study of shape processing in the human visual system has frequently employed radial frequency (RF) patterns as conveniently manipulable stimuli. This study uses an adaptation paradigm to investigate how local shape information is sampled in the processing of RF contour shapes. Experiment 1 measured thresholds for detecting a fixed mean radius RF contour following adaptation to RF patterns which, in separate conditions, varied in mean radius and radial frequency. Results reveal that, adaptation is strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 30 publications
6
39
0
Order By: Relevance
“…Critically, the aftereffect induced by a horizontally compressed adaptor was larger when disparity cues were added (via stereo goggles), resulting in an adapting image that was consistent with viewing an uncompressed shape from an angle (Bell et al, 2008). This result is consistent with our data, although the studies are only weakly analogous.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Critically, the aftereffect induced by a horizontally compressed adaptor was larger when disparity cues were added (via stereo goggles), resulting in an adapting image that was consistent with viewing an uncompressed shape from an angle (Bell et al, 2008). This result is consistent with our data, although the studies are only weakly analogous.…”
Section: Discussionsupporting
confidence: 90%
“…Bell, Dickinson, and Badcock (2008) showed that radial frequency aftereffects can transfer partially between adaptors and tests with different horizontal compressions, consistent with a transfer between shapes viewed from different perspectives.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…A RID can be simulated by appropriate transformation of images using software packages or by writing one's own code 8,10 . Readers wishing to know more about RID can consult relevant texts and websites concerned with viewpoint transformations, or learn about built-in functions in the image processing software of packages such as those listed in our Materials.…”
Section: Simulating a Viewpoint Changementioning
confidence: 99%
“…Changes in viewpoint can occur either when the observer, or the viewed object, moves. Importantly, the viewpoint cost is often reduced by the introduction of stereoscopic cues to the observer [1][2][3][4]6,8 . It is, however, important to distinguish between the rotation of 3D and planar objects.…”
Section: Introductionmentioning
confidence: 99%